2004
DOI: 10.1007/s00068-004-1358-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Salter-Harris Type IV Fracture of the Distal Ulna in a 12-Year-Old Boy

Abstract: Epiphyseal injuries to the distal radius are common in children, but those involving the distal ulna are rare. The most common type of epiphyseal fracture is SalterHarris type II. The authors report on an isolated epiphyseal injury to the distal ulna Salter-Harris type IV, without an associated distal radius injury. To their knowledge, isolated injury Salter-Harris type IV to the distal ulnar epiphysis has not been reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Cannata et al, in a long-term, followup study, reported five such fractures in combination with distal radial metaphyseal fractures, but only one isolated ulnar injury, in a sample of 163 patients [3]. During our extensive literature research, we were able to identify only five cases, two of which were classified as Salter-Harris type IV, one as type III, and two as type II [4][5][6][7][8] (Table 1). In all five cases, the mechanism of injury was described as a fall on the outstretched hand from either a bike or a motorcycle, which is similar to the presented case.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cannata et al, in a long-term, followup study, reported five such fractures in combination with distal radial metaphyseal fractures, but only one isolated ulnar injury, in a sample of 163 patients [3]. During our extensive literature research, we were able to identify only five cases, two of which were classified as Salter-Harris type IV, one as type III, and two as type II [4][5][6][7][8] (Table 1). In all five cases, the mechanism of injury was described as a fall on the outstretched hand from either a bike or a motorcycle, which is similar to the presented case.…”
Section: Discussionmentioning
confidence: 94%
“…The specific anatomical characteristics of the ulnar side of the wrist are thought to be protective for the ulnar epiphyseal plate. The triangular fibrocartilage complex is believed to act as a cushion between the ulna and the proximal carpal row [6]. Moreover, its wide attachment throughout the entire length of the ulnar styloid process propagates the traumatic deforming forces directly to the styloid process, rather than the epiphyseal plate [9].…”
Section: Discussionmentioning
confidence: 99%